Effect of cinnamon extract on blood glucose level and pancreas histopathology in diabetic rats - Nor Adilah , Abdul Ghani; Azzubaidi, Marwan Saad; Al-Ani, Imad Matloub Dally (Department of Anatomy, National University of Singapore, 2016)
The purpose of this research is to evaluate the effect of standardized cinnamon extract (CE) on fasting blood glucose (FBG) level and histopathological changes in islets of Langerhans in streptozotocin-induced diabetic rats (STZ). Twenty ﬁ ve rats were divided into ﬁ ve groups (n=6); normal control, normal treated with “CE” control, diabetic control (non-treated with “CE”), diabetic treated with 200mg/kg CE aqueous extract and diabetic treated with 0.5mg/kg glibenclamide (GLB). All the drugs were given orally as a single daily dose for 30 days. The FBG was determined once per week using Glucometer from rat tail vein. On the ﬁ rst and second week, the 2 groups of diabetic rats treated with CE and GLB showed no signiﬁcant differences of FBG as compared to control group. On the subsequent weeks only GLB-treated group showed no signiﬁcant differences in FBG compared to the normal control. Histology observation revealed that both CE and GLB treated group showing restoration of the normal architecture of the islet structure compared with STZ untreated group which appeared as shrunken islet with degranulated β-cells, and pyknotic nuclei. It is concluded that both CE and GLB treated groups demonstrated signiﬁcantly lower FBG than that of STZ group. CE proved to be effective in reducing FBG in diabetic rats, but it was less potent than GLB.